Vergi ve anayasal düzenlemelerin politik Krizler çağında önemi: 1903-1909 döneminde Osmanlı İmparatorluğu ve Paris Borsası - Avni Önder Hanedar; Mustafa Çalışkan (Turkish Economic Association, 2018)
– This study asks how the Ottoman bondholders traded at the Paris stock exchange evaluated the outcomes of tax and constitutional reforms, based on the data for the most traded bond's price, i.e., the Turkish unified bond, at the Paris stock exchange from 1903 to 1909. The reforms aimed at higher tax income and decreasing arbitrary implications of the Ottoman state. The data are manually collected from The Times. The findings show that the constitutional reform was negatively related to perceived risk of the investors, since there was again a parliamentary system in the Ottoman Empire to blockage the arbitrary policies.
Keywords: G1; N25; N45; 330; Tax reform; Constitutional monarchy; the Ottoman debt management; Price fluctuations; the Turkish unified bond